2019
DOI: 10.24252/bio.v7i1.6352
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Homogenity of Commerson’s Anchovy (Stolephorus commersonnii) in Segara Anakan Cilacap Central Java Inferred from PCR-RFLP Markers

Abstract: Commerson’s anchovy (Stolephorus commersonnii) is a small pelagic fish that live in a group and its existence is very abundant in Segara Anakan Cilacap. This anchovy is widely consumed by communities live around Segara Anakan. This leads to a high exploitation rate. Exploited populations generally have low genetic diversity. This study aims to evaluate genetic diversity of commerson’s anchovy population in Segara Anakan Cilacap inferred from PCR-RFLP of the cytochrome c oxidase 1 (CO1) gene. This study was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Some researchers reported the results of this study were a piece longer than the fragment resulting from the previous studies on Indian marine fishes and Taiwan's fishes species (655 bp), groper Epinephelus sp. (526 bp), and anchovy from Indonesia around 650 bp (Lakra et al 2011;Jefri et al 2015;Bingpeng et al 2018;Nuryanto et al 2019;Tapilatu et al 2021;Dwifajri et al 2022). Whereas the other researchers reported the DNA bands size of the anchovy sample obtained was almost the same as those fishes found in the family Labridae (Dailami et al 2018), marine fishes (Bingpeng et al 2018), Rhincodon typus (Toha et al 2020), Thunnus (Kolondam 2020), even in the gastropod group (Saleky et al 2016;Leatemia et al 2018).…”
Section: Coi Gene Fragment Ampliconmentioning
confidence: 87%
See 1 more Smart Citation
“…Some researchers reported the results of this study were a piece longer than the fragment resulting from the previous studies on Indian marine fishes and Taiwan's fishes species (655 bp), groper Epinephelus sp. (526 bp), and anchovy from Indonesia around 650 bp (Lakra et al 2011;Jefri et al 2015;Bingpeng et al 2018;Nuryanto et al 2019;Tapilatu et al 2021;Dwifajri et al 2022). Whereas the other researchers reported the DNA bands size of the anchovy sample obtained was almost the same as those fishes found in the family Labridae (Dailami et al 2018), marine fishes (Bingpeng et al 2018), Rhincodon typus (Toha et al 2020), Thunnus (Kolondam 2020), even in the gastropod group (Saleky et al 2016;Leatemia et al 2018).…”
Section: Coi Gene Fragment Ampliconmentioning
confidence: 87%
“…The difference among the PCR products from different species could occur, and it is a common phenomenon even though these fragments amplify using a similar primer pair. For example, several previous studies reported different lengths of the COI gene from divergent fish species (Lakra et al 2011;Kusbiyanto et al 2017;Bingpeng et al 2018;Nuryanto et al 2019). It is due to each species having different specific sequences in its genome.…”
Section: Coi Gene Fragment Ampliconmentioning
confidence: 99%